The Analysis of Groundwater Quality for Drinking Purposes: A Case Study of Universitas Muhammadiyah Makassar Area - Abd Rakhim Nanda; Rahmi; Hartono Bancong (Journal of the Civil Engineering Forum, 2023)
The use of groundwater for drinking purposes is increasing along with population growth and the wider range of human activities that require water. Groundwater is used more often because it is more accessible than surface water. The quality of groundwater suitable for consumption as drinking water must pass physical, chemical and biological parameter tests. This study aims to analyze the comparison of groundwater quality at depths of 30 and 100 meters in the area of the Universitas Muhammadiyah Makassar and determine its suitability as drinking water based on physical, chemical, and biological parameters. This research is an experimental study with water sampling collected at two different locations: 30-meter and 100-meter depth wells. In each well, sampling was carried out three times so that there were six total water samples analyzed in total. Data collection was carried out by observation and laboratory tests. Observations were made by looking directly at groundwater conditions to measure parameters such as odor, color, temperature, and pH, while other parameters were tested in the laboratory. The data analysis results showed differences in the values of the physical, chemical, and biological parameters of groundwater taken at a depth of 30 meters and 100 meters. However, the two samples are still within the standard’s allowable range of values. This study concluded that groundwater at a depth of 100 meters in the Universitas Muhammadiyah Makassar area has better water quality than groundwater at a depth of 30 meters. Therefore, if groundwater at a depth of 30 meters is to be used as drinking water with good quality, it must undergo specific treatment.